2022
DOI: 10.1097/ta.0000000000003797
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolic screening in pediatric trauma: A prospective cohort study of risk-stratified ultrasonography

Abstract: This prospective observational cohort study evaluates risk-stratified VTE screening in severely injured children and demonstrates a significant incidence of previously unrecognized, asymptomatic VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…18,19 This is well within the window of when VTEs were usually identified in this study, at about 1 week into an admission, and offers opportunity for education and improvement in implementation; notably, there were no bleeding complications with chemoprophylaxis identified on chart review. That said, with routine ultrasound VTEs in children can be consistently found as early as 3 days after trauma prior to symptoms presenting, 20 which reinforces the needed for prompt and effective chemoprophylaxis strategy.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…18,19 This is well within the window of when VTEs were usually identified in this study, at about 1 week into an admission, and offers opportunity for education and improvement in implementation; notably, there were no bleeding complications with chemoprophylaxis identified on chart review. That said, with routine ultrasound VTEs in children can be consistently found as early as 3 days after trauma prior to symptoms presenting, 20 which reinforces the needed for prompt and effective chemoprophylaxis strategy.…”
Section: Discussionmentioning
confidence: 66%
“…Most importantly, however, is whether chemoprophylaxis is even an effective intervention for children following trauma. While adult data have shown that chemoprophylaxis can reduce the risk of developing trauma-induced VTE in half, 16 it is much more difficult to show efficacy in children given the rarity of diagnosis (although recent studies looking at screening in asymptomatic injured children have shown that VTE rates may be higher than once thought) 20 . Despite this, single-center studies of chemoprophylaxis in critically injured children have shown reduced rates of VTE by 65% 10 ; similar studies looking at children with central lines have shown similar efficacy 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation